2011
DOI: 10.1177/0892020611420597
|View full text |Cite
|
Sign up to set email alerts
|

Teacher self-efficacy and classroom management styles in Jordanian schools

Abstract: Two main purposes guided this study. The first was to identify the degree to which Jordanian teachers practise classroom management styles in their classrooms and their level of teacher self-efficacy. The second purpose was to explore the relationships between classroom management styles and teacher self-efficacy. This study is quantitative in nature and was conducted using a survey design. A variety of statistical techniques were utilised in this research. The Pearson product moment correlation coefficient (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 15 publications
1
37
0
9
Order By: Relevance
“…The researches found signaled the need to understand how self-efficacy is part of the educational context, being influenced by both intrinsic factors, such as those related to class management (Abu-Tineh, Khasawneh and Khalaileh, 2011) or to the student's academic performance (Bandura, 1997(Bandura, , 1998Kaçkaya, 2011;Mojavezi & Tamiz, 2012;Soodak & Podell, 1996), among others as well as by external teaching factors that sometimes impose limits on the teacher's work (Skaalvik & Skaalvik, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The researches found signaled the need to understand how self-efficacy is part of the educational context, being influenced by both intrinsic factors, such as those related to class management (Abu-Tineh, Khasawneh and Khalaileh, 2011) or to the student's academic performance (Bandura, 1997(Bandura, , 1998Kaçkaya, 2011;Mojavezi & Tamiz, 2012;Soodak & Podell, 1996), among others as well as by external teaching factors that sometimes impose limits on the teacher's work (Skaalvik & Skaalvik, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is not by chance that researches have shown positive effects among self-efficacy and various aspects of the teacher's educational context, such as anales de psicología, 2016, vol. 32, nº 3 (octubre) between teaching self-efficacy and academic performance (Anthony & Kritsonis, 2007;Klassen et al, 2011;Mojavezi & Tamiz, 2012), teaching self-efficacy and motivation (NolenHoeksema, Stice, Wade, & Bohon, 2007), teacher selfefficacy and class management (Abu-Tineh et al, 2011); selfefficacy and job satisfaction (Caprara et al, 2006). In this way, Cheung, Richler, Palmeri and Gaultier (2008) postulate that high levels of self-efficacy are positively associated with both the students' academic results and with higher degree of motivation as well as with the belief in their own ability, which is consistent with the idea that teacher self-efficacy was established as a strong predictor of productive teaching practices (Abu-Tineh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otras investigaciones examinan los cambios en la percepción de la autoeficacia del docente incluyendo las modificaciones en las prácticas de enseñanza; las cuales denotan que los docentes que utilizan prácticas más centradas en los estudiantes -2-expanden su sentido de locus de control al impartir instrucción que creen relevante (Abu-Tineh, Khasawneh, y Khalaileh, 2011;Brown, 2005;Eslami y Fatahi, 2008;Friedman y Kass, 2002;Klassen et al, 2009;Mohamadi y Asadzadeh, 2012;Skaalvik y Skaalvik, 2010). Los efectos sobre la enseñanza, derivados de las modificaciones de las estrategias de instrucción, pueden ser significativos para el desempeño de los estudiantes en los países en desarrollo debido a que los docentes principalmente utilizan rutinas diarias muy estructuradas, en las cuales el trabajo individual es monitoreado y ejecutado estrictamente.…”
Section: Introductionunclassified
“…Previous studies have reported that teacher self-efficacy is related to teaching behavior in the classroom (Abu-Tineh, Khasawneh, & Khalaileh, 2011;Hsiao, Chang, Tu, & Chen, 2011;Rahimi & Gheitasi, 2010). Bandura (1997) argued that the collective efficacy of the teachers within a school is a powerful construct that varies considerably among schools and is systematically associated with student achievement.…”
mentioning
confidence: 99%